2013
DOI: 10.1111/j.1365-2265.2012.04480.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between complications and health‐related quality of life in individuals with diabetes

Abstract: Quality of life in patients with diabetes is affected mainly by presence of complications, and not diabetes per se. Peripheral neuropathy was associated with the greatest reduction in quality of life. Improved management to prevent or delay onset of complications may reduce the effect on quality of life in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
60
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 56 publications
12
60
1
5
Order By: Relevance
“…Previous studies in the USA, UK and Singapore also identified that the CVD events were only associated with lower physical aspect of the HRQOL [11,38,39]. Similarly, patients with the presence of CKD had lower SF-12v2 PCS score compared to those without CKD.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies in the USA, UK and Singapore also identified that the CVD events were only associated with lower physical aspect of the HRQOL [11,38,39]. Similarly, patients with the presence of CKD had lower SF-12v2 PCS score compared to those without CKD.…”
Section: Discussionmentioning
confidence: 66%
“…Several cross-sectional studies identified factors associated with HRQOL among Chinese patients with type 2 DM [4,[7][8][9][10][11]. A study on Chinese patients with type 2 diabetes found that being female, older age, having a higher BMI and having DM complications were associated with poorer physical aspects of HRQOL as measured by the SF-12 Health Survey version 2 (SF-12 v2), while being female, younger age, having a lower education level, having a lower BMI and having insulin injections were associated with poorer mental aspects of HRQOL as measured by the SF-12 v2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study also noted the reduction in quality of life among diabetes patients who suffer from various different complications31. Some reports also showed that patients with hand neuropathy reported worse quality of life scores than those without hand neuropathy, based on both objective and patient‐perceived measurements32, 33.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies showed that diabetes had mild to moderate influence on QoL, especially in patients with diabetic complications including polyneuropathy [9][10][11][12] . Physical and mental domains were similarly affected in our patients which is in accordance with few previous studies 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life (QoL) is worse in patients with diabetes who have complications including diabetic polyneuropathy [8][9][10] . Venkataraman et al 11 even found that peripheral neuropathy, among all complications, was associated with the greatest reduction in quality of life. Diabetic patients with neuropathy also have significantly worse trajectory of QoL outcomes over time compared to patients without neuropathy 12 .…”
Section: Introductionmentioning
confidence: 96%